Tertiary Students’ Perspectives on the Use of English Songs and Podcasts on Spotify in Improving Listening Skills - Yuni Marsela; Septi Nurul Aini; Putri Yuliastuti; Rizqah Fajar Khardani; Didin Nuruddin Hidayat; Yatni Fatwa (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The use of multimedia tools has proven beneficial for teaching basic English language skills in our present day. Several studies have demonstrated the result of using one of the media platforms, such as Spotify, where English songs and podcasts can help students learn and develop their listening skills. Despite its efficacy, few researchers have investigated students' attitudes to listening skills using English songs or podcasts on Spotify. The study examines students' perceptions of enhancing their listening skills through Spotify songs and podcasts. Over the academic year 2023/2024, this research was carried out at the Department of English Language Education, UIN Jakarta, with the participation of 10 first-year students. Qualitative description methods have been used in this survey, with data collected from questionnaires and presented by descriptive statistical analyses. The results show that most first-year English Education Department students think that English songs on Spotify are much more effective or beneficial than podcasts for enhancing listening comprehension.